Rip Current-Driven Abrasion: Unveiling Effects on Kota Bani Beach: Abrasi yang disebabkan oleh arus: Mengungkap Dampak yang Terjadi di Pantai Kota Bani - Hestyna Eka Putri; Supiyati Supiyati; Suwarsono Suwarsono (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the impact of rip currents on abrasion at Kota Bani Beach, North Bengkulu Regency. Through direct field measurements of current velocity, wave height, beach slope, and drone photo visualization, we classify Kota Bani Beach as a steep shoreline with up to 18° slope. Significantly, the eroded zone experiences the highest rip current occurrence, featuring current velocities of 1.9 m/s and wave heights of 1.72 m. Our findings underscore the influence of rip currents on beach abrasion, with the eroded zone exhibiting a pronounced susceptibility to rip current occurrence compared to the non-eroded zone. This research highlights the critical role of rip currents in coastal erosion processes, offering valuable insights for coastal management and mitigation strategies. Highlight: Rip Current Impact: Investigating the influence of rip currents on abrasion at Kota Bani Beach reveals a significant connection between these currents and shoreline erosion. Erosion Hotspot: The eroded zone experiences the highest rip current occurrence, characterized by notable current velocities (1.9 m/s) and wave heights (1.72 m). Management Insights: This study underscores the critical role of rip currents in driving coastal erosion, providing essential insights for developing effective coastal management and mitigation strategies. Keyword: Rip Currents, Abrasion, Coastal Erosion, Beach Morphology, Coastal Management